Incidence of premature browning during cooking in ground beef purchased at retail - Hunt, Melvin C.; Killinger, K.M.; Campbell, R.E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We measured the incidence of premature browning during cooking in ground beef that was purchased from retail supermarkets and prepared using common household procedures. Patties made from meat on the outer portion of the packages purchased in the morning had the highest incidence of premature browning (62.5%). Patties from inner portions of packages purchased in the afternoon, refrigerated, and prepared the next morning were more (P<0.05) purple and had the lowest incidence (25%) of premature browning. Overall incidence of premature browning averaged 47%. Because internal cooked color of ground beef is such an unreliable indicator of doneness, temperature measurements should be used to verify that safe endpoint temperatures have been reached.
Keywords: Beef; Premature browning; Retail; Ground beef